WAR ON NAGORNO KARABAKH IN 2020 - THE ROLE OF GLOBAL AND REGIONAL POWERS (Heritage, 2022)
This paper analyzes the war in Nagorno-Karabakh between Armenia and Azerbaijan in 2020, called the Second War and won by Azerbaijan. In addition to the military analysis, research was also carried out on the topic of political, economic and security circumstances that preceded the outbreak of armed conflict, with special emphasis on the role of key foreign policy actors, primarily Russia, Turkey and Iran. Special attention was paid to foreign policy position of the United States on the said conflict. The analysis of the peace agreement, as well as all political and military- security implications that arose from that agreement and that could reflect on the further stability and preservation of peace in the Nagorno-Karabakh region was conducted. The research results indicate that regardless the signed peace agreement and cessation of armed conflicts between the Armenian and Azerbaijani armed forces, Nagorno-Karabakh still remains an area of ​​high conflict potential, and in the future renewed armed conflicts can certainly be expected, at the beginning they could have limited potential, but certainly with a tendency to grow into a new war.
Keywords: Nagorno-Karabakh, Armenia, Azerbaijan, war, drone, aircraft, diplomacy, peace agreement